O mito do presidencialismo brasileiro. E o presidencialismo do mito. (2024)
This paper aims to list the precedents that led to the anti-democratic acts that took place in Brasília on January 8, 2023, with a focus on the functioning of Brazilian presidentialism, especially in the context inaugurated by the 1988 Constitution of the Federative Republic of Brazil. To this end, the research was developed using the inductive method, operationalized through the techniques of operational concept, bibliographic research, and analysis of official national reports. The investigation is justified by the necessary debate that must take place regarding the structure and meaning of the problems within Brazilian presidentialism, in order to offer means of rationalizing and holding the political system accountable, preventing and/or mitigating the effects of crises typical of democratic models. Thus, the anti-democratic acts of January 8, 2023, highlight the dilemma of governance and accountability within Brazilian presidentialism: either being hostage to parliamentary majorities and a broad coalition of parties with no political responsibility or flirting with authoritarian populism, which paves the way for institutional ruptures.